2020
DOI: 10.3390/rs12152507
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Satellite–Terrestrial Connectivity for Autonomous Ships: Survey and Future Research Directions

Abstract: An autonomous vessel uses multiple different radio technologies such as satellites, mobile networks and dedicated narrowband systems, to connect to other ships, services, and the remote operations center (ROC). In-ship communication is mainly implemented with wired technologies but also wireless links can be used. In this survey paper, we provide a short overview of autonomous and remote-controlled systems. This paper reviews 5G-related standardization in the maritime domain, covering main use cases and both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 48 publications
(70 reference statements)
0
24
0
Order By: Relevance
“…Lower operating expenses of autonomous ship alternatives makes them viable for Arctic shipping. With ongoing development in sensor and communication technologies, autonomous ships will soon be able to ensure navigational safety and environmental protection to a degree at least as safe as other conventional shipping routes [45,46].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lower operating expenses of autonomous ship alternatives makes them viable for Arctic shipping. With ongoing development in sensor and communication technologies, autonomous ships will soon be able to ensure navigational safety and environmental protection to a degree at least as safe as other conventional shipping routes [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…The Maritime Unmanned Navigation through Intelligence in Networks (MUNIN) project lead by the Norwegian stakeholders concluded that it is possible to achieve a full degree of automation in ship operations, but a few constraints exist [42]. The constraints include improved sensors and telecommunication technologies than currently used in conventional shipping, the regulatory framework at the national and international level, and cost-effectiveness [45,46]. A critical design factor for the execution of ocean shipping with fully autonomous ships is the implementation of more reliable technical systems on-board, compared to what is applied in present conventional ships [45].…”
Section: Fully Autonomous Shipmentioning
confidence: 99%
See 3 more Smart Citations